Consequences of New IFRS 16 on Firm's Managerial Decision Making and Firm's Value: A Mixed-Methods Study of Indonesia's Transportation and Logistics Sector - Indra Pratama; Ersa Tri Wahyuni; Thaddeus Ezekiel Krisnadi (Indonesian Journal of Islamic Economics and Finance, 2026)
Combining panel-data regression with an embedded qualitative case study, this study examines how the mandatory adoption of IFRS 16/PSAK 116 Leases affects financial ratios, lease liabilities, firm value, and managerial decision-making among Indonesian transport-logistics firms. The quantitative strand analyzes a four-year panel (2018–2021, 88 firm-year observations) drawn from 22 IDXTRANS-listed issuers, while the qualitative strand draws on semi-structured interviews and internal documentation at PT XYZ, a Japanese-invested forwarding company. Wilcoxon Signed-Rank tests show no statistically significant pre- to post-adoption change in the Current Ratio, Debt-to-Equity Ratio, Debt-to-Asset Ratio, ROA, or ROE (all p > 0.05). Panel regression confirms that IFRS 16 adoption significantly increases recognized lease liabilities (β = 0.9769; p < 0.001) and is associated with a modest but significant rise in Tobin's Q (β = 0.2128; p = 0.0011), suggesting investors reward the transparency gain rather than penalizing the higher recognized debt. The PT XYZ case study explains this apparent stability: management responded to the balance-sheet impact with a Rp 35 billion warehouse purchase (substituting ownership for leasing), tightened internal controls after a Rp 2.56 billion double-counting misstatement, and restructured accounting duties — actions consistent with both agency and stewardship motives. Integrating the two strands indicates that the sector-wide “zero effect” on financial ratios is not passive: it is the aggregate outcome of active, firm-level strategic adjustment. The study extends signaling-theory and agency/stewardship-theory explanations of accounting-standard adoption to an emerging-market, lease-intensive industry and offers practical guidance for management, auditors, and DSAK IAI on lease-transition governance.